Gubernamentalidad corporativa y despolitización del reasentamiento de Morococha: una aproximación etnográfica - Miranda, Fabio (2019)
The article describes the process of resettlement in Morococha, in the highland province of Yauli in Junín as well as its historical trajectory as a mining town pivotal to the development of the miningmetallurgic axis in the central highlands of Peru. Additionally, the article critically analyzes mining company discourse that frames the displaced subject and the construction of the sense of community in order to disentangle the terms in which social difference is organized. The article concludes with some insights on the depoliticization of the resettlement process as part of the new forms of corporate governmentality and the gap between endogenous discourses about belonging and practices of identification of affected individuals.